PENGARUH 3D PRINTED POLYCAPROLACTONE HYDROGEL SCAFFOLD KOMBINASI ASAM ELAGAT EKSTRAK KULIT DELIMA TERHADAP JUMLAH SEL ODONTOBLAS PADA TERAPI REGENERATIF ENDODONTIK - Handoko, Monica; Priyanto, Rahmavidyanti (Fakultas Kedokteran Gigi UB, 2025)
Background: Pulp necrosis is a condition in which the pulp of an immature tooth dies partially or completely due to inflammation that must be treated immediately so that root growth does not stop. Recently, regenerative endodontic procedures (REP) have been successfully used to treat necrotic immature teeth. REP is believed to be a biological treatment designed to replace damaged physiological structures of the tooth, including dentin, root structures, and the pulp-dentin complex. Objectives: This study aims to determine the effect of 3D printed polycaprolactone (PCL) hydrogel scaffold combined with ellagic acid from pomegranate peel extract on the increase in odontoblast cells in regenerative endodontic treatment. Methods: The research method used was true experimental with a Post Test Only Randomized Control Group Design. The samples were randomly divided into four groups: a control group induced by pulp necrosis and not given 3D printed PCL hydrogel scaffold, and three treatment groups induced by pulp necrosis and given 3D printed PCL hydrogel scaffold with variations in the ratio of chitosan:ellagic acid 1:10, 2:10, and 3:20. Results: The test results showed an increase in odontoblasts in each treatment group with the most significant increase at a ratio of 2:10. Conclusion: The combination of 3D printed PCL hydrogel scaffold and ellagic acid from pomegranate peel extract influences the increase in odontoblast cells in regenerative endodontic treatment.Keywords: regenerative endodontics, 3D printed PCL hydrogel scaffold, ellagic acid, odontoblast.